Modeling the formation and propagation of desiccation cracks in soils - Sáchez, M.; Manzoli, O. [UNESP]; Guimarães, L. (Crc Press-taylor &francis Group, 2014)
The problem of desiccation cracks in soils has received increasing attention in the last few years, in both experimental investigations and modeling. Experimental research has been mainly focused on the behavior of slurries subjected to drying in plates of different shapes, sizes and thickness. The main objectives of these studies were to learn about the process of crack formation under controlled environmental conditions, and also to better understand the effect of different factors (e.g. soil type, boundary conditions, soil thickness) on the morphology of the crack network. As for the numerical modeling, different approaches have been suggested lately to describe the behavior of drying cracks in soils. One aspect that it is still difficult to describe properly is the crack pattern observed in desiccated soils. This work presents a novel technique to model the behavior of drying soils. The crack patter observed in desiccation tests on circular plates are simulated with the main objective of predicting the effect of soil thickness on crack pattern. Good agreement between experimental results and model prediction are observed. © 2014 Taylor & Francis Group, London.